SARS-CoV-2 Infection as a Cause of Acute Pancreatitis in a Child-A Case Report - Natalia Kopiczko; Kamila Kwiatek-Średzińska; Mirosława Uścinowicz; Monika Kowalczuk-Krystoń; Dariusz Marek Lebensztejn (MDPI AG, 2021)
The novel coronavirus disease (COVID-19) was detected for the first time in China in December 2019. Soon after it was declared a pandemic. Main symptoms include fever, dyspnea, cough, muscle pain, headache, anosmia and ageusia, however a growing body of evidence shows that other organs can be affected. Gastrointestinal manifestations have been observed in a considerable number of patients and include abdominal pain, diarrhea and vomiting. The involvement of liver as well as pancreas has been also described, however there are only a few cases of acute pancreatitis reported in patients with COVID-19. Therefore, we present a case of 6-year-old child with mild acute pancreatitis and COVID-19 pneumonia.